Organizational studies and psychoanalysis: considerations about this trajectory of articulation - Hilda Victória Carrasco; Fábio Vizeu (Revista Eletrônica de Ciência Administrativa, 2024)
The present theoretical essay consists of a brief reflection on the paths hitherto taken by Brazilian researchers in Organizational Studies who have drawn upon Psychoanalysis, and to identify new opportunities for mediating between subjectivity and work. As a criterion for selecting representative texts from this journey, we relied on socio-historical premises to conduct a survey of articles that indicated Brazilian production from this perspective. In the first part, we will present the criteria used for the selection of the texts under analysis, highlighting the selection guidelines used for the construction of the corpus. In the second part, we highlight the main aspects identified in this trajectory, from the French publications that have had the most significant impact on this articulation to the mention of some of the leading national researchers who have drawn from this source. In the third part, we present a synthesis aimed at demonstrating the results found and the main connections discovered. We provide brief comments based on our own journey with Psychoanalysis and Management and propose new research possibilities based on the contribution of Psychoanalysis to the field of Organizational Studies.